Generalized semiflows for a plate model with presumed nonuniqueness of solution - de Sá Teles, Ricardo [UNESP] (Rocky Mountain Mathematics Consortium, 2019)
We study a plate equation with presumed nonuniqueness for the associated Cauchy problem. We establish the existence of global weak solutions by the Faedo–Galerkin method, and our main result refers to the existence of a global attractor using the method of generalized semiflows.
Keywords: Asymptotic behavior of solutions; Global attractor; Nonuniqueness of solution